Wanita 38 Tahun G3P2A0 Dengan HIV/AIDS dan TB Paru - Fenny Harrika; Salmiah Salmiah; Mawaddah Fitria (Inovasi Kesehatan Global, 2025)
Human Immunodeficiency Virus (HIV) is a virus that weakens the immune system. HIV in pregnant women is one of the major health problems that is of concern throughout the world. In this case report, a patient aged 38 years G3P2A0, gestational age 37-40 weeks with complaints of coughing, shortness of breath, weight loss, burning sensation in the mouth in the form of white lesions that almost fill the entire oral cavity. The patient has a history of glandular TB and has received treatment for 6 months in the past 2 years. On the physical examination of the patient, the general condition of the patient was found to be seriously ill, composure of consciousness, blood pressure 100/70 mmHg, pulse rate: 78x/I, respiratory rate: 20x/I, temperature: 36.8ºC, SpO2: 98%, body weight 40 kg and height 157 cm. On examination of the general status of the skin, a reddish rash in the form of small vesicles was found on the right and left arms, back, neck and head. In the mouth and throat, white spots were found in the oral cavity, from the sides of the tongue to the throat. Laboratory investigations showed decreased hemoglobin levels, electrolyte imbalance, hypoalbumin. Serological examination revealed HIV (+) reactivity. Investigation of a PA chest photo showed infiltrate spots at the apex of the left medial lobe. Patients diagnosed with Std IV HIV + oesophageal candidiasis + pulmonary TB + hypoalbuminemia + anemia were given non-pharmacological and pharmacological treatments.